SOSIALISASI PERLINDUNGAN HUKUM OBJEK PEMAJUAN KEBUDAYAAN DALAM AWIG-AWIG DESA ADAT - Jayantiari, I.G.A.M.R.; Aryani, N.M.; Purwani, S.P.; Wirasila, A.A.N. (Buletin Udayana Mengabdi; Vol 23 No 5 (2024): Buletin Udayana Mengabdi, 2023)
The purpose of this service is to socialize the importance of legal protection for objects of cultural advancement that are very close to the life of the customary law community unit. Various cultural traditions in Bali, such as rituals full of values, physical forms of culture as assets of material and immaterial wealth are collective identities that are integrated with traditional villages. The protection of the object of cultural promotion is important for traditional villages in Bali to know, considering that the source of cultural wealth can be found in the customary law community so that it must be accommodated in the local customary law (awig-awig) rules. The targets of this service are the administrators (prajuru), manners, artists and the younger generation (yowana) of the Abiansemal Traditional Village. This service method is a lecture, discussion and question and answer as well as direct coaching by providing concrete instructions to fill in the substance of the wealth of traditional villages in the Abiansemal Traditional Village, Badung Regency. The realization of the service is by implementing the socialization of the inclusion of objects of cultural advancement in the awig-awig of the Abiansemal traditional village and responding directly to the management (prajuru) and local residents (krama) by discussing the substance of the arrangement of village padruwen (village assets) so that the traditional art of the local traditional village protected through the provisions of customary law awig-awig customary village. Keywords: Objects of Cultural Advancement, Legal Protection, Socialization.